2015
DOI: 10.1016/j.ajhg.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-Remodeling-Factor ARID1B Represses Wnt/β-Catenin Signaling

Abstract: The link of chromatin remodeling to both neurodevelopment and cancer has recently been highlighted by the identification of mutations affecting BAF chromatin-remodeling components, such as ARID1B, in individuals with intellectual disability and cancer. However, the underlying molecular mechanism(s) remains unknown. Here, we show that ARID1B is a repressor of Wnt/β-catenin signaling. Through whole-transcriptome analysis, we find that in individuals with intellectual disability and ARID1B loss-of-function mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 49 publications
3
73
1
1
Order By: Relevance
“…The differentiation state of individual cells in spheres and/or different levels of shRNA expression after lentiviral infection may account for this variation. While our study was nearing completion, Vasileiou et al (2015) showed that, as in our study, reducing ARID1B increases Wnt/β-catenin target gene expression. They also overexpressed ARID1B by transient transfection and inhibited Wnt/β-catenin activity in cell lines.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The differentiation state of individual cells in spheres and/or different levels of shRNA expression after lentiviral infection may account for this variation. While our study was nearing completion, Vasileiou et al (2015) showed that, as in our study, reducing ARID1B increases Wnt/β-catenin target gene expression. They also overexpressed ARID1B by transient transfection and inhibited Wnt/β-catenin activity in cell lines.…”
Section: Discussionsupporting
confidence: 71%
“…Also, BRG1 interacts with β-catenin to promote target-gene activation in colon cancer cells (Barker et al, 2001). In patients with intellectual disability, ARID1B represses BRG1 -dependent Wnt/β-catenin signaling (Vasileiou et al, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…(fold regulation of ϽϪ2), except that the bacterial load in ARID1B siRNA-transfected cells increased. ARID1B is an AT-rich DNA-interacting domain-containing protein and a component of the SWI/SNF chromatinremodeling complex, and it has been reported to interact with ␤-catenin to suppress Wnt signaling (49). The results suggest that TRP120 plays a major role in influencing Wnt pathway activation by interacting with these Wnt pathway regulators during E. chaffeensis infection.…”
Section: Gene Activity Analysis Of the Wnt Signaling Pathway In E Chmentioning
confidence: 67%
“…First, the two paralogs seem to associate with different sets of transcription factors (Raab et al, 2015). Second, genetic mouse models suggest that the two proteins are functionally distinct (Celen et al, 2017; Goldman et al, 2016; Krosl et al, 2010; Vasileiou et al, 2015; Zhai et al, 2016). As a matter of fact, we found a subset of 1,817 genes that are not entirely rescued by ARID1B expression and remain dysregulated.…”
Section: Discussionmentioning
confidence: 99%